The Impact of Remittance toward Indonesia’s Economic Growth - Nur Siti Annazah; Ivan Lilin Suryono (Nusantara Science and Technology Proceedings, 2020)
This paper aims to find the impact of remittance on Indonesia’s economic growth. Variable used are remittance, PMTB, import, and economic growth obtained from World Development Indicator (WDI) from 1988 to 2018. Regression analysis of ARDL Cointegration is utilized in finding out remittance, PMTB, and import toward economic growth both for short-term and long-term. The result of the analysis shows that remittance affects long-term economic growth. PMTB variable can increase economic growth both for the short-term and long-term. Import variables can increase economic growth in the short-term, but it decreases economic growth in the long-term. The result shows that external factors need to be paid attention to more by the government because they can contribute toward national economic growth.